Peningkatan Kemampuan Pemecahan Masalah Matematis Melalui Model Pembelajaran Reciprocal Teaching pada Mata Pelajaran Matematika di SD - GUNAWAN, ENCEP ANGGUN; Nahdi, Dede Salim (Papanda Publisher, 2023)
Primary research related to the implementation of the Reciprocal Teaching model to improve students' mathematical problem solving abilities has been carried out a lot. These studies need to be identified, their developments analyzed, and general conclusions drawn so that they can be used as suggestions for the progress of researchers and practitioners in the field of education. This study aims to look at research trends by identifying and classifying all research results related to the application of the mind mapping model to improve student learning outcomes in Indonesia in 2019-2023. This study uses the Systematic Literature Review (SLR) method. There are 10 related articles analyzed in this study. The results of this SLR show that most research on the implementation of the Mind Map learning model on student learning outcomes was carried out in 2020 and the most research subjects were elementary school students. The most widely used research method is the quantitative method and in general the results show that the Reciprocal Teaching model is able to have a positive impact or improve students' writing skills compared to other learning models. The results of this study can be a consideration for researchers in conducting research and for teachers in carrying out learning in the classroom.